Keeping rural children’s hope to stay in the Senior High School through conditional cash transfer: An Indonesian case - Hendrawan Susilo; Setyo Tri Wahyudi (Sebelas Maret Business Review, 2020)
Although the government has allocated cash transfer programs to reduce poverty and improve the education sector, the participation of senior high schools in rural areas in Indonesia is still meager.  This research investigates the relationship between conditional cash transfers in Indonesia (Program Indonesia Pintar–PIP and Program Keluarga Harapan–PKH) with high school participation in children in Rural Indonesia. Using the 2018 socioeconomic survey data released by BPS, we found that children benefited from PIP children had a greater opportunity to participate in high school compared to those who did not. On the other hand, children from PKH beneficiary have a lower chance of attending high school, compared to those who come from families who do not receive PKH. Although conditional cash transfers generally have a positive effect on children's school participation, the success of conditional cash transfers relies on the knowledge of the people about the importance of children's education investments, simple program schemes, secure payment schemes, and efficient and effective technology-based controls.